Solitons in the generalized quantum hydrodynamics and the theory of lightning balls - B. V. Alexeev (Тонкие химические технологии)
Quantum solitons are discovered with the help of generalized quantum hydrodynamics. The solitons have the character of the stable quantum objects in the self consistent electric field. The theory of quantum solitons lead to explanation of the existence of stable atom structures on the microscopic level and lightning balls on the macroscopic level of description of physical systems. The delivered theory demonstrates the great possibilities of the generalized quantum hydrodynamics in investigation of the quantum solitons. The paper can be considered also as comments and prolongation of the materials published in the known author`s monograph (Boris V. Alexeev, Generalized Boltzmann Physical Kinetics. Elsevier. 2004). The theory leads to solitons as typical formations in the generalized quantum hydrodynamics.